2015
DOI: 10.1016/j.infsof.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mirror adaptive random testing through dynamic partitioning

Abstract: a b s t r a c tContext: Adaptive random testing (ART), originally proposed as an enhancement of random testing, is often criticized for the high computation overhead of many ART algorithms. Mirror ART (MART) is a novel approach that can be generally applied to improve the efficiency of various ART algorithms based on the combination of ''divide-and-conquer'' and ''heuristic'' strategies. Objective: The computation overhead of the existing MART methods is actually on the same order of magnitude as that of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…Previous studies [55]- [57] have combined STFCS with static partitioning, using the concept of mirroring to reduce the computational costs. Enhancements to mirroring have included a revised distance metric [91], and dynamic partitioning with new mirroring functions [92]. Chan et al [47] applied bisection partitioning to each dimension of the input domain, then checking the amount of executed test cases in each subdomain: candidates in subdomains with fewer executed test cases were then more likely to be selected.…”
Section: Stfcs + Pbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [55]- [57] have combined STFCS with static partitioning, using the concept of mirroring to reduce the computational costs. Enhancements to mirroring have included a revised distance metric [91], and dynamic partitioning with new mirroring functions [92]. Chan et al [47] applied bisection partitioning to each dimension of the input domain, then checking the amount of executed test cases in each subdomain: candidates in subdomains with fewer executed test cases were then more likely to be selected.…”
Section: Stfcs + Pbsmentioning
confidence: 99%
“…Because ART involves additional computation to evenly spread the test cases over the input domain [17], [18], ART should naturally take more time than RT to generate the same number of test cases, suggesting that it may have worse cost-effectiveness than RT. However, studies [18], [92], [114]- [116] have shown that compared with RT, ART typically requires less time to identify the first failure (F-time) -therefore, ART can be more cost-effective than RT. In general, three main conditions can result in ART achieving a better cost-effectiveness than RT: (a) ART using fewer test cases than RT to detect the first failure (F-measure); (b) the computational overhead of the ART approach being acceptable (comparable or slightly higher than that of RT); or (c) the combined program execution and test setup time being more than the time required by ART to generate a test case.…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that each test case have similar values along the line of mirror dimensions. Huang et al [28] have pointed out that, irrespective of the number of mirror domains implemented in MART, mirroring functions cannot guarantee diversity on all coordinates of mirror test cases. Hence, this is an inherent problem with the use of mapping function of MART.…”
Section: E the Problem With The Mapping Functions Of Martmentioning
confidence: 99%
“…We selected programs with at most four (4) dimensions because the number of MART schemes will be too many and time consuming to analyze if the input dimension is too high. Also, in order to put the performance of EMART into proper perspectives, we adopted twelve (12) programs which have been used extensively [12], [19], [28], [33], [34] in the past to assess the performance of most ART algorithms. These programs were originally written in Fortran Pascal or C; designed for numerical computations and have been converted to C++ programs [6].…”
Section: Emperical Studiesmentioning
confidence: 99%